Pengaruh Struktur Modal dan Pertumbuhan Aset terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening pada Perusahaan Sektor Primer yang Terdaftar di BEI Periode 2019-2023 - Oktafia, Pilsa; Lusiana, Lusiana; Sari, Silvia (Lembaga Yasin AlSys, 2025)
This study aims to see how far the influence of capital structure and asset growth has on firm value with profitability as an intervening variable on primer sector consumer non-cyclicals companies listed on the Indonesian stock exchange for the 2019-2023 period. The population in this study are all consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2019-2023, namely 129 companies. The sample selection technique used purposive sampling and obtained a sample of 32 samples. Methods of data analysis using multiple regression analysis and path analysis in SPSS 26. Based on the hypothesis testing that has been done, it is concluded that the: (1) capital structure have a significant effect on profitability, (2) Asset grwoth has no significant effect on profitability, (3) Capital structure has no significant effect on firm value, (4) Asset grwoth has no significant effect on firm value, (5) Profitability has a significant effect on company value, (6) capital structure has a significant effect on firm value through profitability has an intervening variable, (7) Asset growth has no significant effect on company value through profitability as an intervening variable.